A Hybrid Lumped Parameters/Finite Element/Boundary Element Model to Predict the Vibroacoustic Characteristics of an Axial Piston Pump - Shaogan Ye; Junhui Zhang; Bing Xu; Wei Song; Shiqiang Zhu (Shock and Vibration)
Low noise axial piston pumps become the rapid increasing demand in modern hydraulic fluid power systems. This paper proposes a systematic approach to simulate the vibroacoustic characteristics of an axial piston pump using a hybrid lumped parameters/finite element/boundary element (LP/FE/BE) model, and large amount of experimental work was performed to validate the model. The LP model was developed to calculate the excitation forces and was validated by a comparison of outlet flow ripples. The FE model was developed to calculate the vibration of the pump, in which the modeling of main friction pairs using different spring elements was presented in detail, and the FE model was validated using experimental modal analysis and measured vibrations. The BE model was used to calculate the noise emitted from the pump, and a measurement of sound pressure level at representative field points in a hemianechoic chamber was conducted to validate the BE model. Comparisons between the simulated and measured results show that the developed LP/FE/BE model is effective in capturing the vibroacoustic characteristics of the pump. The presented approach can be extended to other types of fluid power components and contributes to the development of quieter fluid power systems.